1933
DOI: 10.1021/ja01335a034
|View full text |Cite
|
Sign up to set email alerts
|

Ceric Sulfate as a Volumetric Oxidizing Agent. XIV. Indicator Methods for the Standardization and Use of Ceric Sulfate

Abstract: Salstrom's data upon activities was obtained in the case of silver bromide in lithium bromide and sodium bromide. In the case of lithium and potassium salts the deviation from ideality seemed slightly greater for the chlorides than for the bromides.6. The activity coefficients of various salts other than chlorides and bromides might be determined by measurements of e. m. f. in cells otherwise similar to those employed in this research.7. An interpretation of Gtinther-Schulze's observations upon the diffusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1934
1934
2011
2011

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The ceric sulfate solutions were from large supplies made by dissolving ceric ammonium sulfate in 0.5 M sulfuric acid. They had been standardized against Bureau of Standards sodium oxalate (4).…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…The ceric sulfate solutions were from large supplies made by dissolving ceric ammonium sulfate in 0.5 M sulfuric acid. They had been standardized against Bureau of Standards sodium oxalate (4).…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…Blau showed that the ferrous complexes were composed of one mole of ferrous ion combined with three moles of the nitrogen base, and that the oxidation simple conversion to the corresponding ferric complex ion without change of composition. The reaction has been found to be rapid and reversible (8,10). Moreover the complexes are almost completely resistant to any further oxidation.…”
Section: Phenanthroline-ferrous Ion Indicatormentioning
confidence: 95%
“…After removal of the coatings from a 15-g sample, the contents of the first trap was a rigid gel, and a considerable amount of SiCl 4 also was hydrolyzed in the second and third traps. During work with large samples, a liquid, possibly Si 2 C) 6 that formed as a result of a chlorine deficiency during the peak of the silicon carbide and chlorine reaction, condensed in the dry trap, but it completely volatilized by the end of the chlorination. We placed glass wool plugs in the exit bulbs of the first three wet traps to retard uranium and thorium migration.…”
Section: Uranium and Thorium Migrationmentioning
confidence: 99%